Histological typing of tumours of the thymus - Rosai, Juan; Sobin, L. H (Springer, 1999)
The classification represents an effort to bring together the variety of ways thymic epithelial neoplasms have been classified. It focuses on their growth characteristics, i.e. encapsulation and invasion, and cytoarchitectural features, e.g. spindle, epithelioid, and lymphocyte content. The classification, though restricted to the thymic region rather than the mediastinum in general, also covers neuroendocrine, germ cell, lymphoid, and stromal tumours, as well as tumour-like lesions and the neck tumours of thymic or related branchial pouch derivation.
International histological classification of tumours, ISSN 0538-7736
Keywords: onkologie; patologie; nádory brzlíku; Thymus Neoplasms; hyperplazie thymu; endokrinologie; Thymus Hyperplasia